The cryptic complex rearrangements involving the DMD gene: etiologic clues about phenotypical differences revealed by optical genome mapping - Yunting Ma; Chunrong Gui; Meizhen Shi; Lilin Wei; Junfang He; Bobo Xie; Haiyang Zheng; Xiaoyun Lei; Xianda Wei; Zifeng Cheng; Xu Zhou; Shaoke Chen; et al. (Human Genomics, 2024)
Abstract Background Deletion or duplication in the DMD gene is one of the most common causes of Duchenne and Becker muscular dystrophy (DMD/BMD). However, the pathogenicity of complex rearrangements involving DMD, especially segmental duplications with unknown breakpoints, is not well understood. This study aimed to evaluate the structure, pattern, and potential impact of rearrangements involving DMD duplication. Methods Two families with DMD segmental duplications exhibiting phenotypical differences were recruited. Optical genome mapping (OGM) was used to explore the cryptic pattern of the rearrangements. Breakpoints were validated using long-range polymerase chain reaction combined with next-generation sequencing and Sanger sequencing. Results A multi-copy duplication involving exons 64–79 of DMD was identified in Family A without obvious clinical symptoms. Family B exhibited typical DMD neuromuscular manifestations and presented a duplication involving exons 10–13 of DMD. The rearrangement in Family A involved complex in-cis tandem repeats shown by OGM but retained a complete copy (reading frame) of DMD inferred from breakpoint validation. A reversed insertion with a segmental repeat was identified in Family B by OGM, which was predicted to disrupt the normal structure and reading frame of DMD after confirming the breakpoints. Conclusions Validating breakpoint and rearrangement pattern is crucial for the functional annotation and pathogenic classification of genomic structural variations. OGM provides valuable insights into etiological analysis of DMD/BMD and enhances our understanding for cryptic effects of complex rearrangements.